Pathogenic plasticity of Kv7.2/3 channel activity is essential for the induction of tinnitus - Li, Shuang (National Academy of Sciences, 2013)
Tinnitus, the perception of phantom sound, is often a debilitating condition that affects many millions of people. Little is known, however, about the molecules that participate in the induction of tinnitus. In brain slices containing the dorsal cochlear nucleus, we reveal a tinnitus-specific increase in the spontaneous firing rate of principal neurons (hyperactivity). This hyperactivity is observed only in noise-exposed mice that develop tinnitus and only in the dorsal cochlear nucleus regions that are sensitive to high frequency sounds. We show that a reduction in Kv7.2/3 channel activity is essential for tinnitus induction and for the tinnitus-specific hyperactivity. This reduction is due to a shift in the voltage dependence of Kv7 channel activation to more positive voltages. Our in vivo studies demonstrate that a pharmacological manipulation that shifts the voltage dependence of Kv7 to more negative voltages prevents the development of tinnitus. Together, our studies provide an important link between the biophysical properties of the Kv7 channel and the generation of tinnitus. Moreover, our findings point to previously unknown biological targets for designing therapeutic drugs that may prevent the development of tinnitus in humans.